1996
DOI: 10.1111/j.1439-0418.1996.tb01625.x
|View full text |Cite
|
Sign up to set email alerts
|

Bionomics of the four‐eyed spruce bark beetle, Polygraphus rufipennis(Kirby) (Col., Scolytidae) in Newfoundland I. Emergence and flight patterns

Abstract: Emergence patterns and sex ratios of P. rufipennis infesting black spruce were investigated using on‐tree emergence traps. Totals of 242 and 255 beetles (5.0 and 4.0 per 100 cm2) emerged in the traps in 1983 and 1984, respectively. Emergence began on 23 May 1983, and continued for c. 11 weeks; 50% of the adults had emerged by 15 (1983) and 20 June (1984). Generally, fewer beetles emerged as bole height increased. Thinner bark higher in the bole was correlated with decreased beetle emergence and probably reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…in Colorado, are the most common associates of spruce trees infested with Dendroctonus rufipennis. Eleven of the 12 insect species collected in this study have been recorded previously in spruce in Canada, Alaska, and Colorado (McCambridge and Knight 1972;Werner and Holsten 1984;Gara et al 1995;Bowers et al 1996aBowers et al , 1996bPoland and Borden 1998a). To the best of our knowledge Ips grandicollis (Eichoff) (Bright 1976;Wood 1982;Drooz 1985) has not been recorded in Picea previous to this study.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…in Colorado, are the most common associates of spruce trees infested with Dendroctonus rufipennis. Eleven of the 12 insect species collected in this study have been recorded previously in spruce in Canada, Alaska, and Colorado (McCambridge and Knight 1972;Werner and Holsten 1984;Gara et al 1995;Bowers et al 1996aBowers et al , 1996bPoland and Borden 1998a). To the best of our knowledge Ips grandicollis (Eichoff) (Bright 1976;Wood 1982;Drooz 1985) has not been recorded in Picea previous to this study.…”
Section: Discussionmentioning
confidence: 60%
“…These beetles are approximately half the size (Wood 1982) of species such as Dendroctonus rufipennis (Knight 1960;Lister et al 1975;Schmid and Fryes 1977) and Dendroctonus ponderosae (Hopkins) (Amman 1972;Rassmussen 1974) that prefer large diameter trees. Likewise, Bowers et al (1996a) found no difference in emergence of Polygraphus rufipennis at various heights along white spruce boles, and Haack (1984aHaack ( , 1984b found only a weak relationship between diameter and emergence of Ips calligraphus (Germar). Some temporal (Fig.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The present paper describes the host colonization sequence of P. rufipennis. Results relating to emergence and flight patterns are reported seperately ( BOWERS et al, 1996).…”
Section: Introductionmentioning
confidence: 99%